The Role of Motivation and Social Support on Entrepreneurial Mindset in Triguna High School Students in Jakarta - Muhamad Rizki Akbar; Nandang Nandang; Ismail Yusuf (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines the effect of motivation and social support on the formation of an entrepreneurial mindset among students of SMA Triguna Jakarta. The research underscores the importance of fostering entrepreneurial thinking from an early age as a means to cultivate creativity, independence, and resilience in addressing future challenges. Employing a quantitative associative approach, this study examines the relationship between internal and external factors contributing to students’ entrepreneurial development. Data were collected through questionnaires administered to the respondents. The findings indicate that motivation does not have a significant impact on the development of the entrepreneurial mindset, whereas social support exhibits a positive and substantial influence. Support and encouragement provided by parents, teachers, and peers enhance students’ self-confidence, risk-taking ability, and creativity in entrepreneurial endeavors. These results highlight the pivotal role of a supportive social environment in nurturing entrepreneurial attitudes among young individuals. Consequently, collaboration between schools and families is recommended to establish a learning ecosystem that promotes entrepreneurial spirit, competence, and character from an early stage.